2001
DOI: 10.1111/j.1747-6593.2001.tb00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Removal from Groundwater in Conjunction with Biological‐Iron Removal

Abstract: This paper describes an investigation using biological‐iron removal for the elimination of arsenic (III). Groundwater was spiked with sodium arsenite and filtered through a pilot unit. As the water filtered through the sand, arsenic was retained on the iron oxides which were continuously produced by the bacteriological activity. Under specific aeration and pH conditions, both arsenic and iron were eliminated. This process can be used for the design of a full‐scale biological treatment plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Even though the results showed the presence of iron bacteria, a biological arsenic-removal mechanism inside the filters is rather unlikely, mainly because, in that case, removal would also then be observed in the reference filter, i.e., all three filters presented a biological top layer. Among other aspects, the low iron concentration in the inlet was probably the limiting factor for biological arsenic removal in this case, i.e., according to the investigation by Pokhrel et al [17,30], iron must be present in groundwater in concentrations at least 40 times higher than that of arsenic for biological arsenic-removal to be efficient. More detailed investigations would have to be conducted, however, including a more complete analysis of the microbiological population of the other two filters, in order to allow a better understanding of the influence of the biological activities of this type of filters on arsenic removal.…”
Section: Biological Arsenic Removalmentioning
confidence: 82%
“…Even though the results showed the presence of iron bacteria, a biological arsenic-removal mechanism inside the filters is rather unlikely, mainly because, in that case, removal would also then be observed in the reference filter, i.e., all three filters presented a biological top layer. Among other aspects, the low iron concentration in the inlet was probably the limiting factor for biological arsenic removal in this case, i.e., according to the investigation by Pokhrel et al [17,30], iron must be present in groundwater in concentrations at least 40 times higher than that of arsenic for biological arsenic-removal to be efficient. More detailed investigations would have to be conducted, however, including a more complete analysis of the microbiological population of the other two filters, in order to allow a better understanding of the influence of the biological activities of this type of filters on arsenic removal.…”
Section: Biological Arsenic Removalmentioning
confidence: 82%
“…Arsenic removal in conjunction with the biological oxidation of iron or manganese or both has been reported (Lehimas et al, 2001;Zouboulis and Katsoyiannis, 2002a;Katsoyiannis et al, 2002;. Lehimas et al (2001) used natural groundwater and arsenite {As(III)} and ferrous iron was added in pilot scale experiments.…”
Section: Introductionmentioning
confidence: 98%
“…Lehimas et al (2001) used natural groundwater and arsenite {As(III)} and ferrous iron was added in pilot scale experiments. They found that As(III) removal was directly related to the concentration of iron added to the system.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, excess amounts of adsorbents are required to ensure sufficient arsenic removal, which results in the generation of large amount of arseniccontaminated sludge and rising of overall remediation costs 22,23) . To solve such problems, iron-based biological treatments applying iron-oxidizing bacteria (IOB), which has been originally used for Fe and Mn removal from groundwater, have been recently proposed as a cost-effective and environmentally-friendly alternative technology for arsenic removal [24][25][26] . Biogenic iron oxides (BIO) produced by IOB, such as Gallionella ferruginea and Leptothrix ochracea, have been proven to adsorb arsenic efficiently due to their large surface area 26,27) .…”
Section: Introductionmentioning
confidence: 99%